"All I can do is cry" - (:unkn) unknown (My University)
"All I Can Do Is Cry" was a July 2015 report and video by Human Rights Watch documenting the lack of adequate pain treatment for cancer patients in Armenia. It highlighted how bureaucratic, educational, and systemic barriers denied patients palliative care, leaving many in severe, avoidable pain, with only crying as a response
cancer and the struggle for palliative care in Armenia
[Amsterdam : Human Rights Watch, 2015]. - iv, 83 pages : color illustrations, color map ; 27 cm
https://lccn.loc.gov/2016498453
Գիրքը ՀԱԳ- ում բացակայում է։ Տվյալները՝ ԱՄՆ-ի Կոնգրեսի գրադարանից
Keywords: Cancer-Palliative treatment-Armenia; Terminal care-Armenia; Pain-Treatment-Armenia